Structural and functional brain damage in women with multiple sclerosis: A mini-review of neuroimaging sex-based studies - Ceccarelli, Antonia (Frontiers in Neurology, 2022)
Neuroimaging literature in healthy humans has shown that there are sex-related differences in healthy brain's anatomical structure, associated function and susceptibility to neurological diseases. This mini-review summarizes findings derived from the current neuroimaging studies focused on sex-related brain structural and functional damage in women with multiple sclerosis (MS). MS is a chronic, multifactorial, immune-mediated disorder of the central nervous system that affects mostly women. Even if recent neuroimaging studies have shed light on distinctive features of sex-related MS differences in brain structural and functional damage, more research is needed to better elucidate sex-related MS pathological changes and susceptibility and to implement sex-tailored treatment strategies in MS.